1999
DOI: 10.1111/j.1349-7006.1999.tb00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Choline Kinase Activity and Elevated Phosphocholine Levels in Human Colon Cancer

Abstract: Nuclear magnetic resonance spectroscopy has detected elevated phosphocholine levels in human tumor tissues and cells, and in cells that were transformed with the activated Ha-ras gene and stimulated in vitro with growth-promoting factors such as platelet-derived growth factor, epidermal growth factor, and phorbol ester. However, the mechanism of the elevation and the function of the increased phosphocholine levels have not been clearly demonstrated. We studied phosphocholine levels enzymatically and analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 37 publications
2
84
0
Order By: Relevance
“…The elevated phosphocholine levels were due in part to the activation of choline kinase and the increased choline kinase α protein levels. 25) These results suggest that choline kinase and phosphocholine may play a role not only in phospholipid synthesis, but also in regulating cellular growth in cancer cells.This study is the first to analyze choline kinase in DMH-induced rat colon cancer. We further analyzed the mechanism of activation and found that the activation involved increases in both the protein and mRNA levels.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The elevated phosphocholine levels were due in part to the activation of choline kinase and the increased choline kinase α protein levels. 25) These results suggest that choline kinase and phosphocholine may play a role not only in phospholipid synthesis, but also in regulating cellular growth in cancer cells.This study is the first to analyze choline kinase in DMH-induced rat colon cancer. We further analyzed the mechanism of activation and found that the activation involved increases in both the protein and mRNA levels.…”
mentioning
confidence: 83%
“…25,31) Western blot analysis The cytosolic proteins were separated by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis, 32) and transferred onto polyvinylidene difluoride (PVDF) membranes (Millipore Corp., Bedford, MA). Choline kinase α was detected with the affinitypurified anti-choline kinase α antibody and goat anti-rabbit IgG using the ECL reagent as reported previously.…”
Section: )mentioning
confidence: 99%
“…Phosphorylation by choline kinase (CK) constitutes an important step in the incorporation of choline into phospholipids, which is an essential component of all cell membranes. In cancer, there is often an increase in the cellular transport and phosphorylation of choline, as well as an increase in the expression of CK, increasing the uptake of radiolabeled choline (87)(88)(89). Choline can be labeled with either 11 C or 18 F. As a tracer, 11 C-Cho is biochemically indistinguishable from natural choline; however, the short half-life of 11 C has led to the development of 18 F-labeled derivatives, such as 18 F-Fluoromethylcholine ( 18 F-FCho) (90,91).…”
Section: F-fluoromethylcholine ( F-fcho)mentioning
confidence: 99%
“…THE PHOSPHOLIPID PRECURSOR phosphocholine (PCho) has been identified as being a well-validated metabolic biomarker of human cancers including breast, brain, ovarian, gastric, and prostate tumors (1)(2)(3)(4)(5)(6). These tumors have been identified to have significantly higher concentrations of PCho compared to their matched normal tissues.…”
mentioning
confidence: 99%
“…Numerous studies have also demonstrated that 1 H-MRS can be used clinically to diagnose human cancers, monitor responses to therapy, and investigate tumor metabolism by measuring tumor choline metabolites (2)(3)(4)18). These studies have identified changes in tumor choline metabolites as being a key feature of human cancers that can be used to distinguish normal cells from cancer cells (1,7) as well as to assess responses to therapy.…”
mentioning
confidence: 99%